Effects of Socialization Methods and Peer Attachment on Character Strength of School-Aged Children - Risa Umasyah; Alfiasari Alfiasari (Journal of Child Development Studies, 2016)
This study aimed to analyze the influences of socialization methods and peer attachment on character strength of scholl-aged in rural families. This study employed cross sectional approach using survey and interview. A hundred of families with children at grades 4 and 5 in two public elementary schools at Pamijahan Sub District, Bogor Regency participated in this study. This found only age and peer attachment that had significant influence on character strengths of school-aged children in rural families.